Fabrication and application of indium-tin-oxide nanowire networks by polystyrene-assisted growth - Qiang Li (Nature Portfolio, 2017)
Abstract The fabrication and application of polystyrene (PS)-assisted ITO nanowire (NW) networks are reported. The ITO-NW networks are fabricated by means of electron-beam deposition via PS. This method has the advantages of low-temperature (~300 °C), low-cost, facile and efficient operation. The growth mechanism of PS-assisted ITO NWs was analyzed in detail, and the morphology of which could be regulated by the size of PS. X-ray diffraction and high-resolution transmission electron microscope show that the ITO NWs are close to an integral cubic lattice. The transmittance of ITO-NW networks layer is above 90% after 400 nm and the sheet resistance is ~200 Ω/□. When they applied on vertical blue and green LEDs, the light output power all has been improved ~30%. And, the resistive switching behaviors of ITO-NWs were measured and analyzed in Ag/ITO-NW networks/Al capacitor. The application of ITO-NW networks on special morphological devices was discussed. The PS-assisted ITO-NW networks show a strong researching and application value.